2013
DOI: 10.1007/s11412-013-9180-5
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative drawing on a shared digital canvas in elementary science education: The effects of script and task awareness support

Abstract: Creating shared representations can foster knowledge acquisition by elementary school students by promoting active integration and translation of new information. In this study, we investigate to what extent awareness support and scripting facilitate knowledge construction and discourse quality of elementary school students (n=94) in a computersupported collaborative drawing scenario. Students in the awareness condition received feedback prompts based on the characteristics of their drawing. The script foresaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…All in all, current work on CSCL orchestration recognizes the need for aligning scripting and monitoring (Lockyer et al , ; Martínez‐Monés et al , ). However, few proposals make this alignment explicit throughout lifecycle of design, technological deployment, enactment/management and evaluation/assessment of CSCL scenarios (Gijlers et al , ; Magnisalis et al , ). Such alignment would change the way CSCL scripts are designed by educators, as well as the way LA data are collected from CSCL systems and subsequently analyzed for “closing the cycle.” The final goal is providing those educators with valuable awareness information that they can use for orchestration purposes or reflection material about the effectiveness of the enacted script.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…All in all, current work on CSCL orchestration recognizes the need for aligning scripting and monitoring (Lockyer et al , ; Martínez‐Monés et al , ). However, few proposals make this alignment explicit throughout lifecycle of design, technological deployment, enactment/management and evaluation/assessment of CSCL scenarios (Gijlers et al , ; Magnisalis et al , ). Such alignment would change the way CSCL scripts are designed by educators, as well as the way LA data are collected from CSCL systems and subsequently analyzed for “closing the cycle.” The final goal is providing those educators with valuable awareness information that they can use for orchestration purposes or reflection material about the effectiveness of the enacted script.…”
Section: Related Workmentioning
confidence: 99%
“…Several researchers point out the potential synergies that may be derived from aligning both strategies in CSCL, eg, improving the monitorable evidence from the learning scenario (Martínez‐Monés, Harrer & Dimitriadis, ) and providing teachers with data analyses connected to the pedagogical decisions described at design time (Lockyer, Heathcote & Dawson, ). In addition to these conceptual works, there are few technological solutions that support the ad hoc alignment in scripted forums (Magnisalis, Demetriadis & Pomportsis, ) and collaborative canvas (Gijlers, Weinberger, van Dijk, Bollen & van Joolingen, ). Despite the benefits of the alignment envisioned by the theoretical proposals and the positive results identified by the technological solutions, to the best of our knowledge, there is no work dealing with the generic needs of blended CSCL scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Movimento semelhante tem se observado com relação ao interesse pelo uso de aplicações baseadas na web para fins educacionais. Investigações dessa natureza buscam facilitar a interação entre os alunos por meio da utilização de sistemas de comunicação mediada por computador (Gijlers et al, 2013).…”
unclassified
“…Social skills, such as decision making and conflict-managing skills, are considered to be complex and require extensive training. Research into children's social skills during cooperative processes has indicated that younger children especially need training in these skills (Gijlers, Weinberger, van Dijk, Bollen, & van Joolingen, 2013;van Dijk, Gijlers, & Weinberger, 2014), and that this training should occur outside of the cooperative process itself (cf., Saab, van Joolingen, & van Hout-Wolters, 2007).…”
Section: Structuring Heterogeneous Cooperationmentioning
confidence: 99%
“…Transactive dialogue requires children to reflect and act upon each other's reasoning to grasp and process the information. However, research has shown that younger children often experience difficulties with engaging in transactive dialogue and need extensive training to gain these skills (Gijlers et al, 2013;van Dijk et al, 2014 (Zimmerman, 2007). Making these children rely on their own abilities to gather and select knowledge to share could create a dialogue with less information to be shared and learned than might be possible.…”
Section: Domain Knowledgementioning
confidence: 99%